Partial substitution of chemical fertilizer by Trichoderma biofertilizer improved nitrogen use efficiency in wolfberry (Lycium chinense) in coastal saline land - Yan, Kun; Mei, Huimin; Ruan, Yanan; Yu, Shunyang; Su, Hongyan; Zhi, Yibo; Li, Suxin; Sun, Yanan (Frontiers in Plant Science, 2023)
A two-year field trial was conducted to investigate the effects of partial substitution of chemical fertilizer (CF) by Trichoderma biofertilizer (TF) on nitrogen (N) use efficiency and associated mechanisms in wolfberry (Lycium chinense) in coastal saline land. As with plant biomass and fruit yield, apparent N use efficiency and plant N accumulation were also higher with TF plus 75% CF than 100% CF, indicating that TF substitution promoted plant growth and N uptake. As a reason, TF substitution stabilized soil N supply by mitigating steep deceases in soil NH4+-N and NO3–N concentrations in the second half of growing seasons. TF substitution also increased carbon (C) fixation according to higher photosynthetic rate (Pn) and stable 13C abundance with TF plus 75% CF than 100% CF. Importantly, leaf N accumulation significantly and positively related with Pn, biomass, and fruit yield, and structural equation modeling also confirmed the importance of the causal relation of N accumulation coupled with C fixation for biomass and yield formation. Consequently, physiological and agronomical N use efficiencies were significantly higher with TF plus 75% CF than 100% CF. Overall, partial substitution of CF by TF improved N use efficiency in wolfberry in coastal saline land by stabilizing soil N supply and coupling N accumulation with C fixation.